Pengaruh Kepemilikan Manajerial, Karakteristik Dewan, Dan Debt Covenant Terhadap Tingkat Konservatisme Akuntansi (Studi Empiris Pada Perusahaan Manufaktur Yang Terdaftar Di Bursa Efek Indonesia Tahun 2010 â 2012) - Bandi, Bandi; Shintawati, Vidya Ria (STIE Surakarta, 2014)
The purpose of this study is to examine the effect of managerial ownership, board characteristics, and debt covenant on accounting conservatism. Managerial ownershipÂ is measured by the percentage of share ownership by the management company. Board characeristics set uses three proxies, they are the proportion of independent commissioners, board size, and the number of commissioners meeting. Debt covenant is measured using the level of leverage (total debt/total assets). Accounting conservatism as a dependent variable using accrual measure. The research data was extracted from financial statements, annual report, as well as information from other media associated with this research. The sample taken in this research was 65 companies listed on the period of 2010 - 2012. The samples selection uses purposive sampling methods. This study employed a hypothesis test using multiple regression test, partial regression test (t test), the coefficient of determination test (R2), and simultaneous regression test (F test). The results of this study indicate that factors influencing accounting conservatism are managerial ownership, the proportion of independent commissioners, board size, and the number of commissioners meeting and also debt covenant is measured using the level of leverage (total debt/total assets).